MANAJEMEN GUMMY SMILE; SEBUAH TINJAUAN PUSTAKA - Ayu Rahayu Feblina; Hasanuddin Thahir (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Excessive exposure of the gums, especially more than 3 mm while smiling is known as a gummy smile, caused by multifactorial etiology and managed with various techniques. The prevalence of gummy smiles is 10% of the age of the population between 20 – 30 years and is more common in women than men. This review purpose to discuss the best treatment for the gummy smile in relation to the etiologies of the cases, the indication, and contraindication for each treatment. Review: The etiology of a gummy smile is multifactorial, for example, gingival hyperplasia, changes in the eruption of permanent teeth, excess maxillary growth deficiency, lack of lip support produced by marked depression from the maxilla, and hyperactive and/or asymmetrical movements of the upper lip. A gummy smile can be treated by using several techniques, such as orthodontic surgery, gingivectomy or crown lengthening, botox injection, myotomy of the lip elevator muscles, and surgical lip repositioning. A gummy smile can be a significant esthetic concern for patients. Understanding the etiology can be challenging due to the multiple factors that may be concomitantly involved. Accurate diagnosis and treatment planning are critical for proper management. Conclusion: The therapeutic procedure for the gummy smile condition will depend on the etiology and the sincerity of the case that can remove the excess gingival tissue and remodeling to make an aesthetic approach to smile.